EARTHSOS: OUR PLANET, OUR FUTURE - Vimala, Govindaraju; Khadijah, Mohamad Tuah; Nivitha, Baskaran (2025)
The EarthSOS: Our Planet, Our Future volunteer program fosters meaningful and educational engagement between Year 4 students of under the course PBK4204 Campaign and Event Management, Strategic Communication Program, Faculty of Education, Language and Communication, and students of Sekolah Kebangsaan Rakyat, Jalan Haji Bolhassan, Kuching, Sarawak. This project centered around the theme of climate crisis awareness and the program creates a collaborative platform for knowledge exchange and friendly interaction. Through a series of interactive and themed activities, the initiative aims to raise environmental consciousness among primary school students while allowing university participants to apply communication strategies in a real-world context. The program not only nurtures environmental stewardship among young learners but also enhances the civic responsibility and communication skills of the participating undergraduates. The participants were 89 undergraduate students from FELC, UNIMAS and 70 students from SK RAKYAT, Kuching.